Combinatorial algorithms : 27th International Workshop, IWOCA 2016, Helsinki, Finland, August 17-19, 2016, Proceedings /: 27th International Workshop, IWOCA 2016, Helsinki, Finland, August 17-19, 2016, Proceedings. (2016) - Unknown
No abstract available